Zaangażowanie Zgromadzenia Salezjańskiego na rzecz rozwoju społecznego. Wczoraj i dziś - dal Covolo, Enrico (Annales. Etyka w Życiu Gospodarczym, 2010)
This article applies to the social dimension of the Salesian mission. Subject was, chronologically, included in the three points. The article begins with the presentation of the social aspect of the life of the Founder of the Salesians – St. John Bosco. Then it moves to the activity of Bl. Michael Rua and the contribution of other saints, the servants of God and candidates for sainthood from the Salesian Family. The last point indicates a variety of pro-social activities in the above mentioned areas in recent years. This article, of which the author is the Postulator for the Causes of Saints of the Salesian Family, is a contribution to the celebration of 150th anniversary of the Salesian Congregation (1859 – 2009).